The Red Swastika Society’s humanitarian work: a re-interpretation of the Red Cross in China - Pfeiff, Alexandra (New global studies, 2017)
This article examines the emergence of the Red Swastika Society, a Chinese faith-based humanitarian organization, and its development during the 1930s when political changes and war enforced a transformation of the organization and saw a strengthening of its adherence to Red Cross relief activities and Red Cross principles. This article suggests that despite growing similarities with the work of a national Red Cross Society throughout the 1930s, the organization retained its religious founding principles and practices, which distinguished its faith-based humanitarian mission from the larger Red Cross Movement.